EFEKTIVITAS PENYALURAN PEMBIAYAAN KPR SYARIAH BERSUBSIDI PADA PT BANK BTN SYARIAH CIREBON - Suci Aprilliani Utami; Putri Pithaloka Kennedy; Juliana Juliana (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2020)
This research is based on the phenomenon of the problem in which the subsidized Syariah KPR at Bank BTN Syariah is still not on target and has not been utilized by the original debtor or owner. The houses are not occupied or diverted so that the government has not yet become effective in the subsidized Islamic KPR. The purpose of this study is to determine the pattern of the procedure for disbursement of subsidized Syariah mortgage financing at PT. Bank BTN Syariah Cirebon and to find out the level of effectiveness in disbursing subsidized sharia KPR financing to PT. Bank BTN Syariah Cirebon. The population in this study are customers of subsidized Syariah mortgage financing at PT. Bank BTN Syariah Cirebon. The sampling technique used was non-probability-purpose sampling of 96 respondents who had been determined using the Slovin formula. The research method used in this research is descriptive method with a quantitative approach. The data analysis technique used is SPSS 22. The results of the effectiveness of subsidized syariah mortgage financing are the effectiveness of the indicators of use variable 85.3%, target accuracy 84.8%, scope 85.0%, cost effectiveness 85.9%, and accuracy time 81.3%. It can be concluded overall that the effectiveness of Subsidized Syariah KPR financing at PT. Bank BTN Syariah Cirebon is very effective with a yield of 84.5%. Keywords: Effectiveness, Subsidized Syariah KPR, BTN Syariah